Modélisation « macro » de phénomènes dissipatifs localisés à l’échelle « micro »: Formulation et implantation numérique - Brancherie, Delphine; Ibrahimbegovic, Adnan (European Journal of Computational Mechanics, 2004)
In this paper, we present a model capable of taking into account both diffuse dissipative mechanisms taking place at the structure scale and localized dissipative mechanisms taking place at finer scale: the localization zones. This is achieved by introducing in a continuum domain discontinuities of the displacement field. The method proposed herein is capable of combining two types of dissipation: a volumic one taken into account by a classical continuum model and a surfacic one taken into account by the introduction of discrete type laws.